2014
DOI: 10.2174/13816128113199990547
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Upregulates PDCD4 Expression in Patients with Gastric Cancer via miR-21

Abstract: Reactive oxygen species (ROS) plays a key role in carcinogenesis by aberrantly inducing signaling networks that initiatiate tumorigenesis and stimulate tumor progression. MicroRNAs (miRNAs) comprise a novel class of endogenous, small, noncoding RNAs that negatively regulate approximately 30% of the genes in a cell via degradation or translational inhibition of their target mRNAs. However, the effects of ROS on miRNAs expression and the role of miRNAs in ROS-mediated injury on carcinogenesis are uncertain. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…miR-21 expressions was upregulated in gastric cancer tissues than in the adjacent normal gastric tissues. Moreover, expression of PDCD4 in gastric cancer tissues was lower than in adjacent normal gastric tissues [36]. The expression of miR-21 and PDCD4 varied with the degree of gastric cancer differentiation, tumour staging, local lymphatic node metastasis and remote metastasis.…”
Section: Mir-21 and Tumour Suppressor Gene In Gastric Cancer Mir-21 Amentioning
confidence: 90%
See 1 more Smart Citation
“…miR-21 expressions was upregulated in gastric cancer tissues than in the adjacent normal gastric tissues. Moreover, expression of PDCD4 in gastric cancer tissues was lower than in adjacent normal gastric tissues [36]. The expression of miR-21 and PDCD4 varied with the degree of gastric cancer differentiation, tumour staging, local lymphatic node metastasis and remote metastasis.…”
Section: Mir-21 and Tumour Suppressor Gene In Gastric Cancer Mir-21 Amentioning
confidence: 90%
“…Down regulation of mesenchymal markers by miR-21 expectedly suppress the cell proliferation, survival, and invasion of gastric cancer [30]. In vivo studies further revealed that tissues from human gastric cancer showed reduced concentration in anti-oxidation competence (T-AOC), superoxide dismutase (SOD) and catalase (CAT) levels compared to control subjects [36]. miR-21 expressions was upregulated in gastric cancer tissues than in the adjacent normal gastric tissues.…”
Section: Mir-21 and Tumour Suppressor Gene In Gastric Cancer Mir-21 Amentioning
confidence: 96%
“…Aberrant miRNA-21 was found under oxidative stress in GC tissues and GC cells. Further study revealed oxidative stress promoted gastric carcinogenesis according to upregulating miR-21 expression (Tu et al, 2014). Excessive ROS induced by macrophages stimulated the promotion of GC growth according to suppression of miR-328 (Ishimoto et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Supplementation with 50,000 IU vitamin D3 every 14 days for 16 weeks among adult patients with nonalcoholic fatty liver disease did not influence TAC concentrations [42]. Increased inflammatory cytokines and oxidative stress contribute to carcinogenesis through increased production of reactive oxygen species, cell proliferation, and secreting immune suppressors [5-6, 43]. Therefore, vitamin D intake due to its anti-inflammatory and antioxidative actions may be useful to decrease CIN2/3 complications.…”
Section: Discussionmentioning
confidence: 99%